LEARNING IN THE WORKPLACE OF TEACHER EDUCATORS IN THE PHILIPPINES - Dayagbil, Filomena T. (European Scientific Journal, ESJ, 2013)
This research was conceived to find out the learning constructs of teacher educators including what they learned in the workplace, the sources of learning and the factors that motivated teachers to learn. The study revealed that the workplace was a rich avenue for learning where teachers in higher education institutions learned the professional concepts and human relationship skills necessary for effective practice. The teacher educators learned best from self-reflection, printed materials and co-teachers. Other sources of learning were from in-service trainings, administrators and students. What and how teachers learned were influenced by their length of teaching experience. Extrinsic factors like salary, incentives and self-motivating factor like teacher’s commitment motivated the educators to learn.